2009
DOI: 10.1248/bpb.32.269
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Human Immunodeficiency Virus Protease Inhibitor, Nelfinavir, in Poloxamer 407-Induced Hyperlipidemic Model Rats

Abstract: The effect of hyperlipidemia (HL) on the pharmacokinetics of nelfinavir (NFV), a human immunodeficiency virus protease inhibitor, was investigated, focusing on the change of NFV distribution in plasma using poloxamer 407-induced HL model rats (HL rats). The plasma unbound fraction (f u ) in HL rats (0.20-0.39%) was significantly lower than the control (0.92-1.47%). Lipoprotein level in HL rats was about 5 times higher and low-and very low-density liproteins ratio were 1.7-4.5 times higher than the control. NFV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 33 publications
7
18
0
Order By: Relevance
“…reported that the free fraction of nelfinavir, which is a human immunodeficiency virus protease inhibitor and has high binding characteristics to serum lipoproteins such as clomipramine and amiodarone, was not affected by drugs that bind extensively to AAG or albumin. Although the well‐known binding proteins of nelfinavir are AAG and albumin, it is anticipated that nelfinavir binds to lipoproteins for its high lipophilicity [10] . Although there is no information about the contribution of lipoprotein to the total binding of clomipramine in patients, there is a possibility that similar trends of clomipramine in plasma are observed with amiodarone and nelfinavir, because both amiodarone and nelfinavir are basic drugs and have high lipophilicity, such as clomipramine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that the free fraction of nelfinavir, which is a human immunodeficiency virus protease inhibitor and has high binding characteristics to serum lipoproteins such as clomipramine and amiodarone, was not affected by drugs that bind extensively to AAG or albumin. Although the well‐known binding proteins of nelfinavir are AAG and albumin, it is anticipated that nelfinavir binds to lipoproteins for its high lipophilicity [10] . Although there is no information about the contribution of lipoprotein to the total binding of clomipramine in patients, there is a possibility that similar trends of clomipramine in plasma are observed with amiodarone and nelfinavir, because both amiodarone and nelfinavir are basic drugs and have high lipophilicity, such as clomipramine.…”
Section: Discussionmentioning
confidence: 99%
“…The human immunodeficiency virus protease inhibitor nelfinavir and atazanavir, which are high lipophilic and basic drugs, bind well to AAG and lipoproteins. The distribution volume and clearance of nelfinavir and atazanavir in hyperlipidaemic rats were decreased because of the decreasing plasma unbound fraction caused by the increase of lipoproteins [9,10] . Furthermore, the blood clearance of ciclosporin, a highly lipophilic drug, decreased because of the increase of lipoprotein, which is the major complexing constituent for ciclosporin [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Most of these drugs are known to bind extensively (>70%) to plasma proteins (Brocks et al 2006;Brocks and Wasan 2002;Choi et al 2014;Kobuchi et al 2011;Lee et al 2011Lee et al , 2012aLee et al 2012c;Shayeganpour et al 2005;Sugioka et al 2009). Hyperlipidemia induced by P407 is also known to cause a downregulation in the expression of several CYP isoforms in liver of male rats, including CYP3A1/2 and CYP2C11, and decrease in mRNA of several proteins involved in drug transport and metabolism Shayeganpour et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…First, humans and rats demonstrate interspecies differences in terms of lipid metabolism. Rodents are devoid of cholesteryl ester transfer activity, which converts HDL to low‐density lipoprotein 34 ; the major component of plasma lipoproteins in rats is HDL 35 . Moreover, the concentration of Apo E in rat plasma 36 is approximately 5‐fold higher than that in human plasma 37 .…”
Section: Discussionmentioning
confidence: 99%